Study of Composition of Cryopreserved Fragment Extracts From Newborn Piglet Skin and Heart Using Tricine-SDS-PAGE - Bespalova, Irina G.; Rohoza, Liliya A.; Girych, Mykhailo S. (Problems of Cryobiology and Cryomedicine, 2015)
N/A